2021
DOI: 10.18502/wjpn.v4i1.7544
|View full text |Cite
|
Sign up to set email alerts
|

A Survey on Cardiac Complications of COVID-19 in Infants

Abstract: Congenital heart disease (CHD) may have serious effects on the course of COVID-19. Limited data were available on CHD in neonates with COVID-19. This study aimed to review the cardiac complications in neonates infected with COVID-19. Some studies showed that myocardial injury in adult patients is often correlated with a fatal outcome. But, scientific evidence in infants is rare, although several reports were published with the description of cardiac involvement in COVID-19 pediatric patients. In these young su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 53 publications
(80 reference statements)
0
4
0
Order By: Relevance
“…COVID-19 infection in infants has many complications, including cardiac complications. 21,22 Saeedi, et al, compared side effect of survanta and curosurf in decreasing mortality due to RDS in premature infants. They concluded that Survanta and Curosurf are similar in treatment of neonatal RDS.…”
Section: Discussionmentioning
confidence: 99%
“…COVID-19 infection in infants has many complications, including cardiac complications. 21,22 Saeedi, et al, compared side effect of survanta and curosurf in decreasing mortality due to RDS in premature infants. They concluded that Survanta and Curosurf are similar in treatment of neonatal RDS.…”
Section: Discussionmentioning
confidence: 99%
“…The decrease in the incidence of SARS-COV2 in pediatrics, in addition to the greater number of mild and asymptomatic cases, continues to cause problems in determining the appropriate methods of treatment and prevention. 4 The similarity between the spike protein of the coronavirus (protein S) and the ACE-2 receptor, which is located in the heart, intestines, lung epithelial tissue, and kidneys may reveal some of the cardiac involvement of the SARS-COV2 infection. 5,6 In adults, in response to acute infection with COVID-19, high levels of cytokines have caused damage to various organs.…”
Section: Introductionmentioning
confidence: 99%
“…It was first initiated at Wuhan in December 2019. 1,2 The outbreak of SARS-COV-2 has been announced as a global public health emergency by the World Health Organization (WHO). 3 COVID-19 mainly targets the respiratory tract and lungs and the most typical presentations of the infection involve fever, fatigue, dyspnea and dry cough, however gastrointestinal presentations may also be prevalent.…”
Section: Introductionmentioning
confidence: 99%
“…3 COVID-19 mainly targets the respiratory tract and lungs and the most typical presentations of the infection involve fever, fatigue, dyspnea and dry cough, however gastrointestinal presentations may also be prevalent. 1,4 Therefore COVID-19 has a more variable clinical period than the common cold.…”
Section: Introductionmentioning
confidence: 99%